UPAYA MENCIPTAKAN WIRAUSAHA BARU MANDIRI BERBASIS IPTEKS DAN KEARIFAN LOKAL - Hidayati, Nasrul Rofiah; Nuraina, Elva; Isharijadi, Isharijadi (Jurnal Terapan Abdimas, 2016)
IKIP PGRI has always had a commitment to establish an independent mindset in students, for the students equipped with the adaptive ability of science, has leadership and entrepreneurial spirit. Therefore entrepreneurships spirit among the students for the sake of the next generation job creators need to be cultivated. The realization of this commitment IKIP PGRI Madison follow science and technology program for entrepreneurship (IBK) with the aim of developing human potential as young entrepreneurs, independent, based on local knowledge of the higher education and the establishment of outcome-based self-eleven new science and technology entrepreneurs who are ready to do business in community per year, the product of new entrepreneurial students have the advantage of science and technology, better known products produced by student entrepreneurs (PKMK) by the public, increasing the business management of students who have started businesses (oyster mushroom cultivation, the creation of a variety of zipper into a bag and wallet, Pecel Origiri and Yoghurt various flavors) and the publication of the results in the journal IBK entrepreneurship programs. The methods used to recruit participants Ibk tenants based on the success of the team in the delivery of new entrepreneurs Ibk independently in the first year. The number of tenants who started the business in the first year as many as 11 people were divided into 4 groups of businesses. Realization of IKIP PGRI Madison IBK program has accomplished 100%. The work program has been implemented: Socialization, debriefing, internship, start up bussiness, implementation and monitoring of business activities on an ongoing basis by IBK Team PGRI Madison Teachers Training College and a business center complete shop means the student as a student business center, workshop, final report. Pembinanaan process, directing, monitoring and evaluation of business activities will be carried out by a team of tenants and UPPK IBK (Training and Enterprise Development Unit) on a regular basis with the aim to give birth to new entrepreneurs in the IKIP PGRI student Madison as creator of employment generation.Â Keywords: Entrepreneurial self, science and technology, Local Wisdom